1992
DOI: 10.1002/cne.903260407
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of GABAA/benzodiazepine receptor β1, β2, and β3 subunit mRNAs in the developing mouse cerebellum

Abstract: Gamma aminobutyric acid (GABA) is the major inhibitory neurotransmitter in the mammalian cerebellum. Cerebellar granule, Purkinje, and deep nuclear neurons are known to receive GABAergic afferents. Since GABA exerts its inhibitory effects via GABA receptors, it is of interest to determine the temporal relationship between the formation of GABAergic synapses and the expression of genes coding for the GABA receptor. In a previous study, we have examined the developmental expression of binding sites for [3H]musci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 37 publications
2
26
1
Order By: Relevance
“…The developmental pattern of GABAρ subunit localization partially agrees with earlier reports suggesting expression of GABAρ1 and GABAρ2 at low levels in rat Purkinje and Golgi neurons during early postnatal development (30,31). Previous studies have unequivocally demonstrated the presence of other GABA-A subunits (α x β x γ x ) in immature neurons of the cerebellum, and the expression of this receptor is a fundamental element in proper formation of the synaptic circuitry (32)(33)(34). Glial cells are also part of the tripartite synapse, and GABA-A subunits have been identified in Bergmann glia (α 2 γ 1 δ) and EGCs (α 1 ρ 1 ) (9, 10, 35), where they might play a key role as extrasynaptic sensors of GABAergic tone, similar to what occurs in astrocyte-like GFAP + progenitors (36).…”
Section: Discussionsupporting
confidence: 77%
“…The developmental pattern of GABAρ subunit localization partially agrees with earlier reports suggesting expression of GABAρ1 and GABAρ2 at low levels in rat Purkinje and Golgi neurons during early postnatal development (30,31). Previous studies have unequivocally demonstrated the presence of other GABA-A subunits (α x β x γ x ) in immature neurons of the cerebellum, and the expression of this receptor is a fundamental element in proper formation of the synaptic circuitry (32)(33)(34). Glial cells are also part of the tripartite synapse, and GABA-A subunits have been identified in Bergmann glia (α 2 γ 1 δ) and EGCs (α 1 ρ 1 ) (9, 10, 35), where they might play a key role as extrasynaptic sensors of GABAergic tone, similar to what occurs in astrocyte-like GFAP + progenitors (36).…”
Section: Discussionsupporting
confidence: 77%
“…at 260 nm Ϸ 33 µg/ml). The purified oligonucleotides were 3Ј end labeled with [ 35 S] ␣-dATP (Amersham) as described previously (Zdilar et al, 1992). Specific activity of the oligonucleotide probes was approximately 0.8-1.2 ϫ 10 9 dpm/µg.…”
Section: Otx-1 and 2 Oligonucleotidesmentioning
confidence: 99%
“…GABA A receptors develop in approximate spatiotemporal synchrony with GABAergic pathways in the embryonic rat brain [Cobas et al, 1991;Schlumpf et al, 1989;. Transient patterns of GABA A receptor subunit expression have been found in developing rat and primate brain [Gambarana et al, 1991;MacLennan et al, 1991;Frostholm et al, 1992;Laurie et al, 1992a;Poulter et al, 1992;Zdilar et al, 1992;Ma et al, 1993;Fritschy et al, 1994;Chang et al, 1995;Ma and Barker, 1995;Hornung and Fritschy, 1996]. Coordinate development of GABAergic pathways and GABA A receptors has led to speculation that GABA may regulate (modulate) expression of its own receptors [Schousboe and Redburn, 1995].…”
Section: Introductionmentioning
confidence: 99%